2009
DOI: 10.1016/j.crme.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate heat transfer with Large Eddy Simulation for gas turbine components

Abstract: International audienceCHT (Conjugate Heat Transfer) is a main design constraint for GT (gas turbines). Most existing CHT tools are developed for chained, steady phenomena. A fully parallel environment for CHT has been developed and applied to two configurations of interest for the design of GT. A reactive Large Eddy Simulations code and a solid conduction solver exchange data via a supervisor. A flame/wall interaction is used to assess the precision and the order of the coupled solutions. A film-cooled turbine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…The characteristic flow time τ f is of the order of 50 ms while the solid characteristic time τ s is of the order of 10 3 s. The simulation of the flame for several τ s is impractical. The coupling strategy to accelerate the convergence towards steady state is that each domain (flow and solid) is advanced at its own characteristic time using a time step α f τ f for the fluid and α s τ s for the solid with α f = α s [19] . This is equivalent to decreasing the heat capacity of the solid while preserving the conductivity.…”
Section: Coupling Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic flow time τ f is of the order of 50 ms while the solid characteristic time τ s is of the order of 10 3 s. The simulation of the flame for several τ s is impractical. The coupling strategy to accelerate the convergence towards steady state is that each domain (flow and solid) is advanced at its own characteristic time using a time step α f τ f for the fluid and α s τ s for the solid with α f = α s [19] . This is equivalent to decreasing the heat capacity of the solid while preserving the conductivity.…”
Section: Coupling Strategymentioning
confidence: 99%
“…Note that computing the interaction between the flame and the wall requires to compute both the flow and the temperature within the walls simultaneously: the LES code must be coupled with a heat transfer code within the combustor walls. This task is not simple [19,20] because time scales are usually very different (a few milliseconds in the flow and a few minutes in the walls).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic flow time τ f is of the order of 50 ms while the solid characteristic time τ s is of the order of 100 s. The simulation of the flame for several τ s is impractical but it is not needed since the bluff-body temperature changes very slowly and only the steady-state temperature field is relevant here. Therefore, the coupling strategy to accelerate the convergence towards steady state is that each domain (flow and solid) is advanced at its own characteristic time using a time step α f τ f for the fluid and α s τ s for the solid with α f = α s [9] . This is sufficient to obtain steady state values of the cylinder temperature.…”
Section: Coupling Strategymentioning
confidence: 99%
“…Kaess et al [8] proved that the temperature of a laminar flame stabilized in a dump combustor controlled the flame response to acoustic waves. Duchaine et al [9] used sensitivity analysis on a DNS to show that the acoustic response of flames stabilized by a backward facing step depended strongly on the wall temperatures. Mejia et al [3] demonstrated experimentally that controlling the wall temperature of a 2D triangular laminar flame was sufficient to bring it in and out of thermoacoustic oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of heat transfer in the solid combustor parts is performed with the AVTP code [51,52] , which solves the time dependent energy equation:…”
Section: Solid Heat Conduction Solver Avtp and Coupling Strategymentioning
confidence: 99%